If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -5P = 2P + 9 Reorder the terms: 5 + -5P = 9 + 2P Solving 5 + -5P = 9 + 2P Solving for variable 'P'. Move all terms containing P to the left, all other terms to the right. Add '-2P' to each side of the equation. 5 + -5P + -2P = 9 + 2P + -2P Combine like terms: -5P + -2P = -7P 5 + -7P = 9 + 2P + -2P Combine like terms: 2P + -2P = 0 5 + -7P = 9 + 0 5 + -7P = 9 Add '-5' to each side of the equation. 5 + -5 + -7P = 9 + -5 Combine like terms: 5 + -5 = 0 0 + -7P = 9 + -5 -7P = 9 + -5 Combine like terms: 9 + -5 = 4 -7P = 4 Divide each side by '-7'. P = -0.5714285714 Simplifying P = -0.5714285714
| -5/7(-3/28)= | | 5(x+2)=x+24 | | -5/7(-3/8)= | | 5x+a*x=19 | | 6x-27+3x=4+9-x | | g^2-100=0 | | 12u^2+5u-2= | | 4x+5=78 | | y=x^2-3x-8 | | 6y^2+13y+6= | | a-2b=180 | | 16z^2-16z+3=0 | | 25+10(12-K)=5(2X-7) | | 4(x+5)=7-3(x-2) | | (-1xy)*(-1xy)*(-1xy)=(-(1x)*y)*(-(1x)*y)*(-(1x)*y) | | 15p^2+13p+2= | | 32x+12y=8 | | (t+5)(t+5)=(t-3)(t-3) | | 6.56w+9.27=36.4w-5.65 | | (x+1)*(x-5)=0 | | 1.333x+9.333=0.833x+3.833 | | 8m^2+2m=5 | | -3*(x+1)-2*(3-x)=12 | | 96-3x=15x+22 | | 9-10x=75-24x | | 69-2x=2x+9 | | 4-15p=-2p+20 | | 2(m-4)=4(m+2) | | 7b+10=5b+12 | | x+4+8=22 | | 3a-6=2a-11 | | 8(t-4)+4t=4(3t+4)-11 |